Об одном упоминании о белуджах у армянского хроника 18 века - Бояджян, Ваге (Зангак-97)
In this article a passage from a Chronicle by an 18th century Armenian traveler Martiros di Arakel is discussed. For the first time in the Armenian historical sources the name of the Baluch people is attested in the Chronicle. Once again it becomes apparent that the Baluch warlike tribes under the command of Mir-Samandar - the ruler of the Khanate of Kalat, played a considerable role in the military history of Iran and Afghanistan during the late Safavid era. As the Armenian author tells, they acted as allied forces to the Afghan Gilzai tribal confederation in the campaigns against the Persian dominations in the provinces of Kerman and Kashan.
Keywords: Литература